Description of the questionnaire on perceived parental acceptance–rejection (PARQ) - Shurbanovska, Orhideja (Faculty of Philosophy, Skopje, 2018)
Many psychological theories describe the connection between parental behaviour and children and the character traits that develop in them. One of the most prominent theories is Rohner’s Parental Acceptance Rejection Theory (PART). He is the author of several tests describing interpersonal acceptance/rejection between parents and children, parents and their parents, the perception of the parents themselves and their way of parenting, etc. In his manual he presents the original metric characteristics of the tests measuring the perception of acceptance or rejection The aim of this paper is to describe the instruments that measure the child’s perception of parental acceptance-rejection, as well as the metrical characteristics obtained in the tests, adapting them to the Macedonian population. The questionnaires were given to 96 children and 192 parents. The following instruments were adapted: PARQ for children, PARQ for parents, PARQ for adults, PARQ for intimate partners. The following metric characteristics of the tests have been obtained: Cronbach Alpha of PARQ for children for the mother is .906, for the father .93; Cronbach Alpha of PARQ for parents amounts to .823 for the mother, while for the father it is .81, Cronbach Alpha of PARQ for adults for assessment of the mother is .91, while for the father it is .90. Accordingly, there are indications that these instruments could be used for the Macedonian population for research purposes, but also in the clinical practice after the appropriate standardization procedures are implemented.
Keywords: description of the instrument, questionnaires of parental acceptance-rejection, parq for children, parq for parents, parq for adults.